"Probability, Statistics and Queueing Theory with Computer Science Applications" - Allen (Arnold O) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2005)
Probability ; Statistics ; Queuing Theory ; Computer Science Applications
38716a.jpg;38716b.jpg;38716c.jpg
22.5
Keywords: Probability ; Statistics ; Queuing Theory ; Computer Science Applications